KEARIFAN LOKAL DALAM INSTITUSI PUBLIK: STUDI GAYA KEPEMIMPINAN JAWA HASTABRATA PADA SEKOLAH MENENGAH DI KABUPATEN JEMBER - Asri Sundari (LITERASI: Indonesian Journal of Humanities, 2014)
This study aims to understand the process of social construction of hastabrata’s leadership local wisdoms on school principals that has referred to the formal legal leadership stipulated on Ministerial Decree No. 28 of 2010. The research results reveal that the leadership style of the principals who have only based on formal legal rules Ministerial Decree No. 28 of 2010 give poor performance. When the principals apply local knowledge of hastabrata give results in the forms of morality, manners, ethics as contained in 8 hastabrata teachings, namely the character and nature of the symbols of earth, wind, water, moon, sun, sky, fire, and star. Therefore, leadership basing on local knowledge of hastabrata can be applied in relation to the management of human resources, including the relationship with superiors, subordinates, internal or external work units because the modern leadership requires the mastering of science and technology, faith, and obedience. Keywords: hastabrata, local wisdoms, principals, leadership